Client construction in front-line social work practice : a technological perspective - Barneis, Reuven (1982)
The research is an organisational study of front-line social work practice with clients in two area offices. The aim of the study is to analyse how area office social workers understand, and work with clients. Most social workers work in organisational settings as area offices. One aim of the study is to evaluate environmental constraints on front-line social work practice with clients. To this effect, the study looks at how social workers construct understandings of and work with clients. All clients come to the area office with rich personal histories and circumstances. Prom this biographical background, social workers abstract information that they consider relevant to their work with clients. The research found that workers in each area office construct understandings of and work with clients according to shared work routines. These routines vary between offices for the same type of client. The Metropolitan Office is responsible for social work services in a rapidly changing urban area. The research found that social workers in this office work with clients on the basis of established work routines. There are few exceptions to these work patterns. Because of a large referral rate, and because social workers use nearly exclusively a casework technology in their work with clients, the office has developed a hierarchal system of management with inflexible work routines. Although the office is responsible for services in an urban area undergoing rapid architectural, economic and social changes, social workers in this office work with clients according to these inflexible work routines within hierarchal organisational structure. In contrast to the Metropolitan Office, the Suburban Office is responsible for social work services in a relatively stable, residential community. Because of a small referral rate, the office has developed a less hierarchal system of management with relatively more flexible work routines. However, because of a steady rise in unemployment, increasing demands are being made on the office's casework technology. As a result, the area office's social workers are discussing the possibility of re-dividing area office manpower to include an intake team. Because the re-division is intended to ensure the continued use of the office's casework technology, specialist services such as community work wiih elderly and mentally handicapped clients and community work in general are being curtailed. The major difference between the two area offices is their different referral rates. As the referral rate in the Suburban Office increases, decisions are being made that establish less flexible work routines and structure a more hierarchal area office management system. One important finding is that when increased demands'are made on office's casework technology, the office adopts less flexible work routines and a more hierarchal management structure to ensure continued use of its casework technology. .Area office social workers do not search for new technologies in response to environmental changes. If area office social workers use casework as their primary work technology, it is a work technology that is viable in stable environments only. If pressures on this technology increase, area office social workers have the choice to either searching for a new work technology or restructuring the area office to ensure the continued use of casework. Because of organisational constraints they usually choose the latter option